Development of micromechanical model of asphalt mixture in complex form for dynamic modulus characterization - Bin Liu; Junlin Yang; Kai Zhang; Xiangyang Fan (Frontiers in Materials)
Asphalt mixture is a multiphase composite viscoelastic material, with its fundamental viscoelastic properties primarily determined by its material composition and internal microstructure. The application of composite micromechanics and the development of mathematical models to predict the mechanical performance of asphalt mixtures are of great significance. However, existing self-consistent micromechanics models primarily focus on the magnitude of the complex modulus of asphalt mixtures, often neglecting the phase angle. To more comprehensively evaluate the viscoelastic mechanical properties of asphalt mixtures, this study extends the self-consistent model to its complex form. By predicting the storage modulus and loss modulus of the mixture, the goal of simultaneously predicting the dynamic modulus and phase angle is achieved. The effectiveness of the model was validated using four types of asphalt mixtures through forward and inverse modeling approaches. By integrating inverse and forward solutions within the complex micromechanical model, the dynamic modulus and phase angle can be accurately predicted. The coefficients of determination between the predicted results and the measured data are all above 0.9, demonstrating the model’s robust predictive capabilities.